Anti-Naturalism and Structure in Interpretive Social Science. Issue 3 (2nd October 2019) - Wedeen, Lisa
ABSTRACT: Mark Bevir and Jason Blakely's Interpretive Social Science: An Anti-Naturalist Approach successfully points out the problems with various forms of philosophical naturalism, demonstrating how essentialism, synchrony, and an effort to establish lawlike generalizations bedevil social science on both sides of the interpretive/positivist divide. The authors do an excellent job of identifying the philosophical roots and debates that are tied to the interpretive turn, while offering a thought-provoking critique of Michel Foucault. However, Bevir and Blakely overstate the degree to which Foucault's work succumbs to forms of naturalism more typical of empiricist social science. Although this is certainly a problem in Foucault's work, the book too readily dismisses his important analysis of deep social structures, which cannot be reduced to individuals' ideas. Interpretive Social Science also overlooks relevant debates in feminist theory and existing criticisms of political culturalism, raising questions about the book's intended audience.